2012
DOI: 10.1002/psp.1730
|View full text |Cite
|
Sign up to set email alerts
|

Couples' Education and Regional Mobility – the Importance of Occupation, Income and Gender

Abstract: People with high education are more geographically mobile than people with lower education. Further, highly educated men are more mobile than highly educated women, and the man's education affects couples' migration propensities more than the woman's. This study examines whether the reasons for the higher migration propensities among highly educated people are the occupational characteristics and income commonly associated with high education. Further, the study examines whether the reason for the asymmetric e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 51 publications
2
32
2
Order By: Relevance
“…In addition, Swedish families with young children of a school age have a greater preference for living near family and relatives and a lower propensity to migrate (Branden, 2013;Niedomysl, 2008). However, this is contrary to an Italian study, which found that family commitments actually increase migration probability (Nifo and Vecchione, 2014).…”
Section: Demographicscontrasting
confidence: 58%
See 1 more Smart Citation
“…In addition, Swedish families with young children of a school age have a greater preference for living near family and relatives and a lower propensity to migrate (Branden, 2013;Niedomysl, 2008). However, this is contrary to an Italian study, which found that family commitments actually increase migration probability (Nifo and Vecchione, 2014).…”
Section: Demographicscontrasting
confidence: 58%
“…However, if there are wage differences in her type of job between regions, migration propensity increases. On the other hand, this does not hold true for men (Branden, 2013).…”
Section: Demographicscontrasting
confidence: 46%
“…The location of educated 'talents' has been given top priority as a local survival strategy, especially considering the continued down-sizing and flexibilisation of the labour force in most notably the automotive industry and its related spinoffs. The public sector remains a very large employer, in part due to a constant urbanization process paralleled with the growing responsibilities of the local municipalities and the comparatively high share of female labour participation in Sweden (Andersson, 1987;Brande´n, 2013). There are also signs of a growing number of individuals employed within creative occupations, and a structural change of the Swedish economy over the last 20 years.…”
Section: Gothenburg and Norra ä Lvstrandenmentioning
confidence: 97%
“…An incipient literature has begun to question the role of occupational structures and regional contexts of opportunity in shaping the migration behaviour of family households (Nisic 2009;Shauman 2010;Brandén and Ström 2011;Perales and Vidal 2013). Analysing Swedish data, Brandén (2013) finds that the fact that men's education affects family migration decisions more than women's is due to a higher concentration of women in occupations with low wages and career potential. Using British data, Perales and Vidal (2013) show that gender asymmetries in the impact of spousal resources on family migration decisions are channelled by structural inequalities in the labour market (such as occupational sex-segregation).…”
Section: Structural Perspectives and Early Cross-national Researchmentioning
confidence: 99%